2021
DOI: 10.21037/qims-20-246
|View full text |Cite
|
Sign up to set email alerts
|

Value of quantitative dynamic contrast-enhanced and diffusion-weighted magnetic resonance imaging in predicting extramural venous invasion in locally advanced gastric cancer and prognostic significance

Abstract: Background: Extramural venous invasion (EMVI) has been found to be related to poor prognosis in gastric cancer. Preoperative diagnosis of EMVI is challenging, as it can only be detected by surgical pathology. The present study aimed to investigate the value of quantitative dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and diffusion-weighted imaging (DWI) in predicting EMVI preoperatively, and to determine the relationship between prediction results and prognosis in patients with locally advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…This was consistent with most studies in nasopharyngeal carcinoma, GC, oesophageal carcinoma, rectal cancer and cervical carcinoma. 7 , 8 , 13 , 17 , 18 The V e value of T3 and T4 stage was higher than that of T1+2 stage, indicating that as the degree of malignancy increased, EES volume fraction also increased, so more intravascular fluid entered the EES to ensure adequate nutrition and oxygen supply for the tumor. 8 In addition, this study found that V e is the best parameter for identifying T staging (accuracy is 0.788), which is better than CT and ultrasound (accuracies are 0.715, 0.678, respectively).…”
Section: Discussionmentioning
confidence: 96%
“…This was consistent with most studies in nasopharyngeal carcinoma, GC, oesophageal carcinoma, rectal cancer and cervical carcinoma. 7 , 8 , 13 , 17 , 18 The V e value of T3 and T4 stage was higher than that of T1+2 stage, indicating that as the degree of malignancy increased, EES volume fraction also increased, so more intravascular fluid entered the EES to ensure adequate nutrition and oxygen supply for the tumor. 8 In addition, this study found that V e is the best parameter for identifying T staging (accuracy is 0.788), which is better than CT and ultrasound (accuracies are 0.715, 0.678, respectively).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, DCE-MRI has been proven useful in predicting the histological type and Lauren classification of the tumor and estimating tumor angiogenesis in GC [ 7 ]. It can also predict extramural venous invasion preoperatively in local AGC [ 10 ]. Unlike the abovementioned studies, which used conventional imaging analysis, we used a histogram analysis based on DCE-MRI in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Different quantitative parameters such as volume transfer constant (Ktrans), reverse reflux rate constant (Kep), extracellular extravascular volume fraction (Ve), and plasma volume fraction (Vp) can be obtained in DCE-MRI [ 8 ]. At present, DCE-MRI has proven to be reliable in predicting extramural venous invasion and patient prognosis and monitoring antiangiogenic therapies [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative DCE-MRI was performed by using multiphase axial 3D spoiled-gradient recalled-echo sequences for liver acquisition with volume acceleration-extended volume (LAVA-XV) sequence with breath-hold. According to our previous study ( 19 ), pre-contrast T1 mapping with four different flip angles (3°, 6°, 9°, and 12°) was acquired before dynamic scanning for the determination of pre-contrast T1 values. Then a dynamic scan with 42 consecutive phases was performed, which shared the scanning parameters and range as T1 mapping, with a flip angle of 15° and temporal resolution of 6 s/phase.…”
Section: Methodsmentioning
confidence: 99%
“…The signal intensity on MRI was converted into an equivalent concentration of contrast material using the variable flip angles method. The pharmacokinetic parameters including volume transfer constant (K trans ), reverse reflux rate constant (k ep ), extracellular extravascular volume fraction (v e ), and plasma volume fraction (v p ), which were derived from DCE-MRI, were calculated using the two-compartment extended Tofts model as described in our previous study and report ( 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%